2019
DOI: 10.1002/ece3.5810
|View full text |Cite
|
Sign up to set email alerts
|

Organic farming expansion drives natural enemy abundance but not diversity in vineyard‐dominated landscapes

Abstract: Organic farming is seen as a prototype of ecological intensification potentially able to conciliate crop productivity and biodiversity conservation in agricultural landscapes. However, how natural enemies, an important functional group supporting pest control services, respond to organic farming at different scales and in different landscape contexts remain unclear. Using a hierarchical design within a vineyard‐dominated region located in southwestern France, we examine the independent effects of organic farmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 47 publications
(64 reference statements)
2
31
2
Order By: Relevance
“…We found spider abundances not to be affected by the proportion of semi-natural habitats and we detected a non-significant positive trend with increasing crop diversity. Such effects contradict some recent results (Garratt et al, 2017;Opatovsky et al, 2017;Pompozzi et al, 2019), but these seem to indicate that the abundances of ground-dwelling spiders are affected not only by the noncrop habitats in the landscape (Muneret et al, 2019).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We found spider abundances not to be affected by the proportion of semi-natural habitats and we detected a non-significant positive trend with increasing crop diversity. Such effects contradict some recent results (Garratt et al, 2017;Opatovsky et al, 2017;Pompozzi et al, 2019), but these seem to indicate that the abundances of ground-dwelling spiders are affected not only by the noncrop habitats in the landscape (Muneret et al, 2019).…”
Section: Discussioncontrasting
confidence: 86%
“…A possible explanation is that the value of semi‐natural habitats for beneficial arthropods is dependent upon other local and landscape features. Local crop management such as within field rotation, fertilizer and pesticide applications, or the characteristics of field surroundings such as cropland composition, might strongly drive the level of pest control provided by natural enemies (Muneret et al., 2019; Ricci et al., 2019; Tscharntke et al., 2016), limiting the expected benefits of having abundant semi‐natural habitats in the landscape (Gagic et al., 2019; Rundlöf, Smith, & Birkhofer, 2016). Moreover, semi‐natural habitats may be more important for the temporal stabilization of resource availability in landscapes with simplified crop regimes (Schellhorn et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Native cover-crop species enhanced arthropod diversity in South African vineyards [ 26 ] and natural enemy abundance and predation on light brown apple moth in Australia [ 63 ]. Furthermore, predator abundances of spiders, earwigs, and ants are negatively affected by tillage intensity [ 24 , 64 , 65 ]. Moreover, higher L. botrana infestations were recorded in vineyards which were frequently tilled compared to those planted with cover-crops in Italy [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, neither egg predation nor pupae predation was affected by landscape composition. Similarly, L. botrana infestation and predator abundance were not affected by proportion of seminatural habitats in France [ 19 , 64 ], while L. botrana egg predation even decreased with increasing proportion of seminatural habitats [ 11 ]. In the same region, Papura et al [ 31 ] showed that harvestmen (which are important predators of grape berry moths) populations increased with increasing proportions of seminatural habitats at the landscape scale.…”
Section: Discussionmentioning
confidence: 99%
“…Predator communities of the vineyard foliage were sampled three times in 2015 (between June and September; N = 124: 3 × 42 vineyards and two plots with missing values). At each sampling date, predators were sampled by beating 30 vine stocks in each vineyard (Muneret, Auriol, Bonnard, et al., 2019). All predators were stored in 70% ethanol and individuals were identified at the lowest possible taxonomic resolution.…”
Section: Methodsmentioning
confidence: 99%